210Po and 210Pb disequilibrium at the PN section in the East China Sea. (August 2017) - Su, Kaijun; Du, Jinzhou; Baskaran, Mark; Zhang, Jing
Abstract: Lead-210 and 210 Po have been widely used as tracers for quantifying particulate scavenging in the upper layer of the oceanic water column. In this study, we investigated the 210 Po/ 210 Pb disequilibrium in the water column of the PN section in the East China Sea (ECS) during autumn 2013. In most of the water column, a deficiency of 210 Po was observed with respect to its parent nuclide 210 Pb (i.e., a 210 Po/ 210 Pb activity ratio < 1.0). The ( 210 Po/ 210 Pb)dissolved, ( 210 Po/ 210 Pb)particulate and ( 210 Po/ 210 Pb)total activity ratios ranged from 0.29 to 0.71 (average: 0.53 ± 0.13, n = 27), 0.31 to 1.42 (average: 0.70 ± 0.27, n = 27) and 0.22 to 0.62 (average: 0.50 ± 0.12, n = 27), respectively. The distribution coefficients ( K d ) of 210 Po and 210 Pb were 12.1× 10 4  ml g −1 and 8.8× 10 4  ml g −1, with an average ( 210 Po/ 210 Pb)total activity ratio of (0.50 ± 0.12, n = 27). However, over the continental shelf, planktonic detritus and fecal pellets appear to be the main carriers for 210 Po, which preferentially scavenges 210 Po and produces a lower ( 210 Po/ 210 Pb)total activity ratio (0.49 ± 0.12, n = 22) with a K d for 210 Po of 13.8× 10 4  ml g −1 in the water column. The variations in the fractionation factor (1.48 ± 0.66) of 210 Po/ 210 Pb reveal distinct differences between the distribution and scavenging of 210 Po and 210 Pb by particulate matter in different marine environments: in the estuarine zone (a high turbidity area), terrigenous suspended particulate matter scavenges 210 Pb from the water column, while in areas dominated by biogenic particular matter, 210 Po is preferentially scavenged from the water column. Using the 210 Po/ 210 Pb disequilibrium in the water column, we estimated the removal fluxes of POC from the upper waters downward to be 25.0 mg C m −2 d −1, comparable to those in other marginal seas. Moreover, a decreasing trend of POC removal fluxes was observed with increasing distance offshore. Highlights: 210 Po was deficient relative to 210 Pb in all stations. Mean T 210 Po/T 210 Pb activity ratio was ∼0.50. There was a significant inverse correlation between Kd and TSM. Fluxes of 210 Po and POC show decreasing with offshore distance.